Ionic conductivity and related studies of polymer electrolytes based on poly(E-caprolactone) / Woo Haw Jiunn - Woo, Haw Jiunn (2013)

(untitled)
Poly(E-caprolactone) (PCL)-based polymer electrolytes (PE) were prepared by solution casting. PCL has excellent properties of biocompatibility and biodegradability leading to wide applications in the biomedical field. In this work, PCL was used as a polymer host to reduce environmental impact. Ammonium thiocyanate (NH4SCN) salt was incorporated as the source of charge carriers. Ethylene carbonate (EC) was added as the chain lubricant to enhance ionic conductivity of the PE system. Two systems (PCLNH4SCN and PCL-NH4SCN-EC) were prepared and characterized by using differential scanning calorimetry (DSC), scanning electron microscope (SEM), x-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy and electrochemical impedance spectroscopy (EIS). The pure PCL exhibited ionic conductivity of 1.86 x 10-10 S cm-1 at room temperature. The highest conductivity of PCL-NH4SCN system was 3.94 x 10-7 Scm-1 with addition of 26 wt.% NH4SCN. A further conductivity enhancement was observed with addition of EC to the highest conducting PCL-NH4SCN sample. The highest conductivity of PCL-NH4SCN-EC system was 3.82 x 10-5 S cm-1 at 50 wt.% EC concentration. Vogel-Tamman-Fulcher (VTF) fitting of the temperature dependent conductivity showed that the ionic motion was coupled with polymer segmental motion. The addition of EC had improved the dissociation rate of free ions and also made the polymer chain more flexible to facilitate ionic motion. Deconvolution of the SCN- stretching mode of the FTIR spectrum reveals that the increase in salt concentration results in the increase in number density of free ions. On the other hand, the incorporation of EC was observed to dissociate contact ion pairs and ion aggregates contributing to more free ions. FTIR analysis also demonstrated interactions between PCL and NH4SCN, PCL and EC and between EC and NH4SCN through appearance of new shoulder, changes in peak intensities and shifts in peak position. Incorpoaration of iv EC has introduced new pathways with shorter jump distance for the cation to move from one complex site to another. VTF fitting showed that the calculated pseudo energy of PCL-NH4SCN-EC system was one order lower than PCL-NH4SCN system. The complexation in the PCL-NH4SCN and PCL-NH4SCN-EC systems were supported by DSC studies. The melting enthalpy calculation shows an increase in amorphousness in the two systems. However, the glass transition temperature, Tg was found to increase gradually in the PCL-NH4SCN system but decreased drastically in the PCL-NH4SCNEC system. The semi-crystalline nature of the PE films was revealed by XRD. When the sharp crystalline peaks were decomposed from the broad amorphous spectrum, the relative degree of crystallinity was estimated and the values obtained were in agreement with DSC results. EC molecules were trapped into the polymer matrix and disrupting some regions of the crystalline phase. From morphology studies using SEM, large spherulites were observed for pure PCL film. As more salt was incorporated to PCL until 26 wt.%, the number of spherulite was observed to increase with a reduction in their size. Upon addition of EC, the clear spherulite boundaries faded away and eventually showed a homogeneous smooth surface.